PENTAKOSTALISME DAN TEORI SOSIAL KONTEMPORER : PENTECOSTALISM AND CONTEMPORARY SOCIAL THEORY - Elia Tambunan (Sekolah Tinggi Teologi Satyabhakti, Malang)
The Pentecostal Movement is recognized for its contribution to global church growth and contemporary social theories. But by his own people pentecostalism is often positioned only as a revival, experience with the Holy Spirit, and divine healing which in its development becomes associated with eschatological issues. In terms of methodology, Pentecostal scholars outside Indonesia analyzed Pentecostalism based on religious and theological perspectives with the approach of ritual theory and spirituality studies. Theologians, activists, and intellectuals as well as Pentecostal scholars in Indonesia also have not developed Pentecostal studies further methodologically. They have not used methodological work to develop a study of the Pentecostal movement into a useful framework for theoretical study or field research in the existing membership colleges. On the contrary, by social scientists it utilizes Pentecostals as the main object of research on social phenomena but is only limited to the study of the dimensions of religious experience. By prioritizing the study of English literature and presenting statistical results of field survey research, this paper intends to develop a study of Pentecost in Indonesia methodologically. This paper shows how to understand Pentecostal phenomena from the perspective of social theory. The author first reads the literature on Pentecostalism, especially the one produced by Poloma and then constructs itself and then integrates it with social theory integrally. Then, the writer will classify it in three broad outlines, namely the Pentecostal religious experience of religious psychology; Pentecostal dimensions: symbolic, ritual, ceremony and institution from the perspective of comparative theory of religion; and community and Pentecostal popularity from the perspective of religious sociology. From here it will be seen the contribution of Pentecostals as both the object of precisely the study society and scientific methodology combined with contemporary social theories. This can be used by theologians, activists, and intellectuals as well as Pentecostal scholars in Indonesia specifically to develop studies of the Pentecostal movement in Indonesia specifically. ==== Gerakan Pentakosta diakui kontribusinya terhadap pertumbuhan gereja secara global maupun teori-teori sosial kontemporer. Namun oleh kaumnya sendiri pentakostalisme seringkali diposisikan hanya sebagai kebangunan rohani, pengalaman dengan Roh Kudus, dan kesembuhan ilahi yang dalam perkembangannya menjadi dikait-kaitkan dengan persoalan eskatologis. Dari sisi metodologi, sarjana Pentakosta di luar Indonesia menganalisis Pentakostalisme berdasarkan perspektif agama dan teologi dengan pendekatan teori ritual dan studi spiritualitas. Para teolog, aktivis, dan intelektual maupun sarjana Pentakosta di Indonesia juga belum mengembangkan kajian Pentakosta secara metodologis lebih lanjut. Mereka belum menggunakan kerja metodologis untuk mengembangkan kajian gerakan Pentakosta menjadi kerangka pikir yang bermanfaat dalam kajian teoritis maupun penelitian lapangan di sekolah-sekolah tinggi kepentakostaan yang ada. Sebaliknya, oleh ilmuwan sosial justru memanfaatkan kaum Pentakosta sebagai objek utama penelitian tentang fenomena sosial namun baru sebatas kajian terhadap dimensi pengalaman beragama. Dengan cara mengutamakan studi literatur berbahasa Inggris serta menampilkan hasil statistik penelitian survei lapangan, tulisan ini bermaksud untuk mengembangkan kajian tentang Pentakosta di Indonesia secara metodologis. Tulisan ini memperlihatkan bagaimana memahami fenomena Pentakosta dari perspektif teori sosial. Penulis terlebih dahulu membaca literatur tentang Pentakostalisme khususnya yang dihasilkan Poloma dan kemudian mengkonstruksi sendiri lalu memadukannya dengan teori sosial secara integratif. Kemudian, penulis akan mengklasifikasikannya dalam tiga kerangka pikir secara garis besar, yakni pengalaman keagamaan Pentakosta dari psikologi keagamaan; dimensi Pentakosta: simbolik, ritual, seremoni dan institusi dari perspektif teori perbandingan agama; dan komunitas dan popularitas pentakosta dari perpektif sosiologi agama. Dari disini akan terlihat kontribusi kaum Pentakosta baik sebagai objek tepatnya masyarakat kajian maupun metodologis keilmuan berpadu dengan teori-teori sosial kontemporer. Ini bisa digunakan oleh para teolog, aktivis, dan intelektual maupun sarjana Pentakosta di Indonesia secara khusus untuk mengembangkan kajian gerakan Pentakosta di Indonesia secara khusus.